INVESTIGATIONS INTO THE ACCURACY OF THE UAV SYSTEM DJI MATRICE 300 RTK WITH THE SENSORS ZENMUSE P1 AND L1 IN THE HAMBURG TEST FIELD - T. Kersten; J. Wolf; M. Lindstaedt (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
The development of increasingly powerful Unmanned Aerial Vehicles (UAV) is progressing continuously, so that these systems equipped with high-resolution sensors can be used for a variety of different applications. With the Matrice 300 RTK, Da-Jiang Innovations Science and Technology Co. Ltd (DJI) has launched a system that can use the high-resolution camera Zenmuse P1 or the laser scanner Zenmuse L1 as a recording sensor, among other sensors. In order to investigate the geometric quality of these two sensors, HafenCity University Hamburg, in cooperation with LGV Hamburg, NLWKN in Norden and the German Archaeological Institute in Bonn, flew over the 3D test field in the Inselpark in Hamburg-Wilhelmsburg on 5 August 2021 with the P1 camera and the L1 laser scanner. Using the Matrice 300 RTK as carrier platform, the test field was recorded in various configurations at altitudes between 50 m and 90 m above ground. Prior to the UAV flight campaign, 44 marked ground control points (GCP) were signalised in the test field, which had already been surveyed by LGV in 2020 using geodetic measurement methods to achieve a coordinate accuracy of ±5 mm for each GCP. The results of aerial triangulations as well as 3D point clouds generated from image data and laser scanning are compared with reference data in order to demonstrate the accuracy potential of these measurement systems in this paper.